RAMSAY HUNT SYNDROME: A CASE REPORT - Made Ayu Dessy Dwitasari; Desak Made Cittarasmi Saraswati Seputra (MNJ (Malang Neurology Journal), 2023)
Ramsay Hunt Syndrome (RHS) is a rare disease caused by reactivation of latent Varicella Zoster Virus in the geniculate ganglion which lead to inflammation, edema, and compression of facial nerve. RHS may affect both immunocompetent and immunocompromised patient. Clinical manifestation of RHS include herpes zoster oticus that manifest as vesicular rash on auricular area or oral mucosa in combination with peripheral nerve palsy. We reported a 67-years-old female patient with herpetic vesicle on left side of face and ear accompanied with ipsilateral peripheral facial paralysis since 2 days before admission. Patient was treated with acyclovir for 5 days. Follow up examination showed satisfying clinical improvement with disappearance of vesicles and otalgia, as well as facial weakness improvement from House Brackmann grade III to grade II. Early recognition and treatment of Ramsay Hunt Syndrome is crucial as delay of treatment may lead to sequelae, including postherpetic neuralgia and permanent facial paralysis.